2001
DOI: 10.2535/ofaj1936.77.6_189
|View full text |Cite
|
Sign up to set email alerts
|

Long Descending Lymphatic Pathway from the Pancreaticoduodenal Region to the Para-aortic Nodes: Its Laterality and Topographical Relationship with the Celiac Plexus

Abstract: In 6 of 15 postmortem-treated cadaveric specimens, we found macroscopically thick lymphatic collecting vessels that originated from not only the nodes along the common hepatic artery (No. 8 nodes) but also from the pancreaticoduodenal region, and which drained directly into the para-aortic nodes immediately below the left renal vein (No. 16b1-inter or -latero nodes). The collecting vessels, if they originated from the ventral (dorsal) visceral side, passed to the left (right) of the superior mesenteric and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…It showed a difference of 6.54 in favor of the RAMPS group with a p<0.00001. Pancreatic lymph node drainage pathways and mapping are of interest for a long time (22)(23)(24)(25)(26)(27)(28). Previous studies and new data were included and described in detail in O'Morchoe's paper (3).…”
Section: Discussionmentioning
confidence: 99%
“…It showed a difference of 6.54 in favor of the RAMPS group with a p<0.00001. Pancreatic lymph node drainage pathways and mapping are of interest for a long time (22)(23)(24)(25)(26)(27)(28). Previous studies and new data were included and described in detail in O'Morchoe's paper (3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the paraaortic lymph node station is important in pancreatic lymphatic drainage. 45,46 Indeed, occurrence of para-aortic LNM has been associated with LNM in more proximal nodes such as stations 13, 14 and other peripancreatic lymph nodes. 26,29,47 The method to estimate mean survival times using reported medians, ranges and sample sizes has been widely used and validated.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has limitations, as the goal is complete excision of the tumor with a margin of normal tissue in addition to regional lymph nodes. Several studies have described the drainage and nodal stations important for the pancreas [19,[34][35][36][37][38][39][40], and this has subsequently been reviewed [41]. In 2003, Strasberg et al [22] described a technique to improve visibility, remove the N1 nodal stations, and permit adjustment in the depth of the posterior extent of the resection during surgery.…”
Section: Pancreatic Adenocarcinoma-body and Tailmentioning
confidence: 99%